VIOLÊNCIA PSICOLÓGICA CONJUGAL EM UNIVERSITÁRIOS: ESTUDO DE FATORES DE RISCO - Sacramento, Lívia de Tartari e (2007)
This study broaches on violence as defined by the World Health Organization (KRUG, 2002). We also use the Straus and Sweet (1992) definition of Psychological Violence. Our general goal was to identify the occurrence of matrimonial psychological violence among University students and correlation to risk factors. The specific goals were to verify any correlation between this and participants self-esteem, alcohol intake, age group, number of children and family income. Respondents could be of either genre, should be married or in a stable union, be aged between 16 and 60, as well as being students at Universidade Metodista de São Paulo (UMESP). The field research was conducted at UMESP and included students from undergraduate courses as well as other higher education courses. This is a descriptive research with a non-probability sample, determined by convenience. The instrument was answered by 246 people, chosen based on the sample inclusion criteria, all of whom had immediate availability to answer the instrument. Among the respondents, there were more women (145) than men (100). The instrument was composed of Conflict Tactic Scale Form R (CTS1), Rosenberg s Self-Esteem and Self-Concept Scale as well as an Adapted Social-Demographic Questionnaire. CTS1 was used to measure family violence, the Self-Esteem Scale verified people s positive or negative attitude towards themselves, while the questionnaire supplied supplementary data on personal and matrimonial information of respondents. 246 instruments were analyzed through the Statistical Treatment SPSS 13 for Windows. The results showed that approximately 30% of the respondents of both genres and the entire sample had a high level of psychological violence. We verified a tendency: the lower the self-esteem, the higher the level of psychological violence. We also found evidence that there is no linear correlation between this factor and the habit of alcohol intake or the quantity of alcohol consumed by respondents. This data is not corroborated by the researched literature, therefore, we found that alcohol in itself says little as a risk factor for the occurrence of psychological violence. Its articulation merits further planning and investigation by means of knowledge and actions which will contribute to the health of the population. We concluded that marital psychological violence is many times seen as trivial and made commonplace.